Abnormalities in the GABAergic Inhibitory System Leading to the Development of Spike-Wave Discharges in the Somatosensory Cortex of WAG/Rij Rats - Nejad, G.G.; Vastyanov, R.S.; Shahabi, P.; Alipoor, M.R.; Pakdel, F.G. (Нейрофизиология, 2015)
We investigated the effects of muscimol on generation of spike-wave discharges (SWDs) and short-term plasticity alterations in the somatosensory cortex of WAG/Rij rats. The rats were implanted with a twisted tripolar electrode into the above cortex region and with an intraventricular cannula into the right cerebral ventricle. EEG recordings were made before and after muscimol and saline injections. Paired-pulse stimulations (200 µsec, 100-1000 µA, 0.1 sec⁻¹) were applied to the somatosensory cortex at 50-, 100-, 400-, and 500-mseclong intervals for 50 min. Pharmacological amplification of GABAergic transmission in the somatosensory cortex exerted an inhibitory effect on the thalamo-cortical circuit underlying the generation of spike-wave discharges (SWDs). Ten minutes post-injection of muscimol, paired-pulse facilitation was significantly reduced at 50- and 100-msec-long interpulse intervals (P < 0.05). The data obtained suggest that muscimol suppresses generation of SWDs and changes short-term plasticity via imitation of the effects of GABA in inhibitory synapses.